179k views
2 votes
HELP PLS: If f(x) = 2x – 3 and g(x) = 2x2 + 5x + 1, find:
a. f(4) + g(1)

HELP PLS: If f(x) = 2x – 3 and g(x) = 2x2 + 5x + 1, find: a. f(4) + g(1)-example-1
User Marykay
by
5.0k points

2 Answers

3 votes

Answer:

Explanation:

User Roel Van Westerop
by
4.3k points
7 votes

Answer:

13

Explanation:

f(x) = 2x - 3,

f(4) = 2(4) - 3,

f(4) = 5

g(x) = 2x^2 + 5x + 1,

g(1) = 2(1)^2 + 5(1) + 1,

g(1) = 2 + 5 + 1,

g(1) = 8

f(4) + g(1) =

5 + 8 =

13

Hope this helps :)

User Antonius Common
by
4.8k points